Sosialisasi Dasar-Dasar Komputer di SDN Neglasari - Nugraha, Muhamad Fahmi; Yanti, Lina Dwi; H, M. Fachri; P, Nadia Rosmaya (Ma'soem University, 2025)
This community service activity aims to provide a basic understanding of computers for elementary school students in an effort to improve technological knowledge from an early age. This activity was carried out at SDN Neglasari, Kutawaringin Soreang. The problem to be solved is the lack of a basic introduction regarding the components, functions, and operation of computers for elementary school students. The methods used in this activity include discussion, educational video screenings, direct observation of computer hardware, and hands-on practice for turning on, turning off, and using a computer. Through the implementation of this community service, it is hoped that students can understand the function of computers in daily life , recognize their main parts , and operate them wisely. The result of this activity is to open students' views regarding the importance of computer technology that can support the learning process and facilitate daily activities.